RESEARCH ON REDUCTIVE BURNING STEEL MELTING DUST (European Journal of Interdisciplinary Research and Development, 2025)
The present paper is based on experimental data obtained by the author and represents the results of a comprehensive experimental and theoretical investigation into the phase composition, microstructure, and physicochemical properties of steel melting dust formed during steelmaking processes. The study considers steelmaking dust generated in electric arc furnace (EAF) operations as a representative case. Samples of dust were collected from various stages of the technological cycle, including dust collection systems and post-treatment residues, and were analyzed using modern analytical techniques. The objectives of this study are twofold: first, to investigate the phase distribution of valuable components such as iron and zinc in steel melting dust; and second, to elucidate the mechanisms governing metal recovery and losses during reductive burning. The obtained results provide a scientific basis for developing effective technologies aimed at improving the utilization of steelmaking dust through optimized reductive burning conditions, thereby enhancing metal recovery and reducing environmental impact. The findings are of interest to researchers and industrial specialists engaged in secondary raw material recycling, metallurgical waste processing, and the development of sustainable steel production technologies.